Learning at school through to university: the educational experiences of students with dyslexia at one UK higher education institution. Issue 4 (22nd April 2022) - Jacobs, Lisa; Parke, Adrian; Ziegler, Fenja; Headleand, Chris; De Angeli, Antonella
Abstract: Dyslexia is a specific learning disability affecting 1 in 10 people nationwide. Literature acknowledges the need for greater understanding of the educational needs of learners with dyslexia in UK Higher Education (HE). Research in this field often stems from neuropsychological viewpoints and neglects the perspectives of students. This study was designed to understand the lifelong learning experiences of students with dyslexia. Semi-structured interviews were conducted with fourteen students. Transcripts were analysed using interpretative phenomenological analysis. Three superordinate themes were identified: ' Managing Feelings of Inferiority', ' Adapting to the Learning Environment ', and ' Experience of Learning Support '. Analysis highlighted the range of challenges students face throughout education. Findings suggest that HE institutions need to be more effective in creating an inclusive learning environment that supports this underrepresented group. This will facilitate a reduction in the social and emotional barriers to learning and educational attainment for this population. Points of interest: This article provides an in-depth understanding of the lifelong learning experiences of students with dyslexia in Great Britain. Students with dyslexia continue to experience social, emotional and academic barriers to learning. University undergraduates and postgraduates with dyslexia find it difficult to adjust to learning in HE but they have developed their own strategies to help. This research found that technology does not always meet the learning needs of individuals with dyslexia, and students in HE often do not use it. Research needs to understand why students are not using technology to support their learning, and determine how to improve it. Students in this study felt that their university needs to improve the learning support services available to them on campus, for example, one-to-one academic support and wellbeing drop-in services should be offered.